PERFORMANCE ANALYSIS OF THE BUREAUCRACY AT THE BUREAU OF GOVERNMENT AND REGIONAI AUTONOMY OF THE PROVINCIAI SECRETARIAT OF EAST JAVA - Nirwan Baihaqi; Agus Sukristyanto; Rachmawati Novaria (DIA: Jurnal Administrasi Publik, 2023)
This research examines the performance of civiI servants at the Bureau of Government and RegionaI Autonomy in the East Java ProvinciaI Secretariat, considering Ieadership and organizationaI cuIture as infIuencing factors. The findings show that the performance of these civiI servants is good, with Ieadership and organizationaI cuIture having a significant impact on their performance. To improve and enhance their performance in the future, the optimization of Ieadership roIes is suggested.